The Mimetic Strand in the Cello Literature Within the Context of History, Instrument Design, Iconography and Cello Performance - Mizia, Urszula (Ars Musica. Interdisziplinaere Studien, 2020)
This book is the first integral study of the history of imitative or co-creative artistic work that has led to the creation of cello transcriptions and arrangements. Of an interdisciplinary character, it explores the views that have shaped approaches to the art of cello performance and describes the role of cello transcriptions and the development of instrument making. The book also addresses issues related to philosophy, history of aesthetics and visual arts, including iconography presenting historical images of the cello. The theoretical part contains definitions and systematics that make it possible to categorise the vast amount of transcriptions, as well as descriptions and suggested recordings of a selection of those transcriptions.